Effect of Mobile Health on Obese Adults: A Systematic Review and Meta-Analysis - Park, Seong-Hi; Hwang, Jeonghae; Choi, Yun-Kyoung (Healthcare informatics research, 2019)
This study was conducted to examine the effects of mobile health (mHealth), using mobile phones as an intervention for weight loss in obese adults. An electronic search was carried out using multiple databases. A meta-analysis of selected studies was performed. The effects of mHealth were analyzed using changes in body weight and body mass index (BMI). We identified 20 randomized controlled trials (RCTs) involving 2,318 participants who fit our inclusion criteria. The meta-analysis showed that body weight was reduced with a weighted mean difference (WMD) of -2.35 kg (95% confidence interval [CI], -2.84 to -1.87). An examination of the impact of duration of intervention showed that weight loss was greater after 6 months of mHealth (WMD = -2.66 kg) than between three and four months (WMD = -2.25 kg); it was maintained for up to 9 months (WMD = -2.62 kg). At 12 months, weight loss was reduced to a WMD of -1.23 kg. BMI decreased with a WMD of -0.77 kg/m (95% CI, -1.01 to -0.52). BMI changes were not statistically significant at 3 months (WMD = -1.10 kg/m ), but they were statistically significant at 6 months (WMD = -0.67 kg/m ). The use of mHealth for obese adults showed a modest short-term effect on body weight and BMI. Although the weight loss associated with mHealth did not meet the recommendation of the Scottish Intercollegiate Guideline Network, which considers a reduction of approximately 5 to 10 kg of the initial body weight as a successful intervention. Well-designed RCTs are needed to reveal the effects of mHealth interventions.